A case of kidney infection by Corynebacterium pseudotuberculosis in sheep - PAPAIOANNOU (Ν. ΠΑΠΑΪΩΑΝΝΟΥ), N.; ZAVLARIS (Μ. ΖΑΒΛΑΡΗΣ), M.; GIADINIS (Ν.Δ. ΓΙΑΔΙΝΗΣ), N. D.; PETRIDOU (Ε.Ι. ΠΕΤΡΙΔΟΥ), E. J.; PSYCHAS (Β. ΨΥΧΑΣ), V. (Journal of the Hellenic Veterinary Medical Society, 2017)
A three year-old female sheep was presented to the Clinic of Farm Animals, School of Veterinary Medicine, Aristotle University of Thessaloniki, with mild nasal seromucous discharge and progressive weight loss, while rectal temperature was normal. Hematological examination revealed mild leukocytosis, while traces of hemoglobin and protein were found in urinalysis. The animal was euthanized and forwarded for necropsy. An extremely enlarged, nodular right kidney, whose renal parenchyma was completely replaced by multiple abscesses, was the remarkable finding of the necropsy. Microbiological and molecular examinations were performed to establish the diagnosis and rule out Maedi/Visna infection. Tissue samples from the kidney and other organs were, also, examined histologically. Corynebacterium pseudotuberculosis was isolated in microbiological tests. A kidney infection by C. pseudotuberculosis, presented as a clinical case with scant symptoms, is discussed in this case report.